Challenges and strategies for bio-based and biodegradable plastic waste management in Europe - Žaneta Stasiškienė and Jelena Barbir and Lina Draudvilienė and Zhi Kai Chong and Kerstin Kuchta and Viktoria Voronova and Walter Leal Filho (Sustainability, 2022)
In recent years, an increasing trend towards replacement of conventional fossil-based plastics with bio-based plastics was noticed, i.e., production of plastics partly or fully made from biomass is rapidly expanding. Currently, bio-based and biodegradable plastics have a very small market size, approximately only 1% of all plastics produced. However, the forecast of the global bioplastics production capacities predicts an increase from approximately 2.417 million tonnes in 2021 to approximately 7.593 million tonnes in 2026, more than three times the current capacity. Therefore, it is necessary to assess the challenges and identify the barriers for bio-based and biodegradable plastics for waste management and to evaluate the effectiveness of current plastic waste management strategies for the efficient waste management of bio-based and biodegradable plastics. The main barriers and motivators of the biodegradable and biodegradable plastics market that have been identified include macroeconomic factors, regulatory factors, technological factors, and social factors. The bio-based and biodegradable plastics have to be separately collected and treated under mostly controlled, regulated conditions. However, currently, there are no legal provisions providing for the separate collection of bio-based plastics, leading to their disposal with either hazardous waste, conventional plastics, or municipal waste. Since the effective plastic waste management strategy relates to good performance in each step of the waste management process, bio-based and biodegradable plastic waste management could, therefore, be based on an effective strategy for the management of plastic waste. However, there is a need for standardizing waste collection systems and creating a harmonized waste collection infrastructure, which would lead to effective sorting of bio-based plastic waste.
Keywords: bio-based and biodegradable plastics market; bio-economy; bioplastics sector; waste management strategy